2018
DOI: 10.1007/s13202-018-0437-4
|View full text |Cite
|
Sign up to set email alerts
|

Research on heavy oil gas lift assisted with light oil injected from the annulus

Abstract: An experimental study on the multiphase flow of heavy oil gas lift was conducted on 18.25 m high vertical tube. Based on the experimental results and the wellbore heat transfer mechanism, a coupling model of wellbore pressure-temperature gradients was presented for the gas lift with light oil injected from the annulus. Moreover, the solution of coupling annulus flow with tubing flow was also established through cyclic iteration. Experimental results showed that gas injection enables heavy oil and light oil to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Figure shows the shortcomings of the commonly used heavy oil viscosity reduction methods at present. For example, Heating viscosity reduction consumes a lot of energy. The diluted oil mixed with the diluted viscosity reduction method needs to be dehydrated in the early stage before it can be mixed with the heavy oil, and the mixed liquid after production needs to be dehydrated again. The ultrasonic propagation distance used in the ultrasonic viscosity reduction method is limited, which limits its effectiveness. Microbial viscosity reduction method has high requirements for microorganisms, which narrows its application. Although the emulsification viscosity reduction method has been widely used in the oil industry, it still has certain challenges. This is because the anionic surfactant has poor salt-resistance and is easy to precipitate with high valence cations in crude oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the shortcomings of the commonly used heavy oil viscosity reduction methods at present. For example, Heating viscosity reduction consumes a lot of energy. The diluted oil mixed with the diluted viscosity reduction method needs to be dehydrated in the early stage before it can be mixed with the heavy oil, and the mixed liquid after production needs to be dehydrated again. The ultrasonic propagation distance used in the ultrasonic viscosity reduction method is limited, which limits its effectiveness. Microbial viscosity reduction method has high requirements for microorganisms, which narrows its application. Although the emulsification viscosity reduction method has been widely used in the oil industry, it still has certain challenges. This is because the anionic surfactant has poor salt-resistance and is easy to precipitate with high valence cations in crude oil.…”
Section: Introductionmentioning
confidence: 99%
“… 8 11 The diluted oil mixed with the diluted viscosity reduction method needs to be dehydrated in the early stage before it can be mixed with the heavy oil, and the mixed liquid after production needs to be dehydrated again. 12 14 The ultrasonic propagation distance used in the ultrasonic viscosity reduction method is limited, which limits its effectiveness. 15 18 Microbial viscosity reduction method has high requirements for microorganisms, which narrows its application.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation results of the model were compared with the measurement results of the field sensors, and the results showed that the model has good accuracy. [15] conducted an experimental study on annular injection of light oil-assisted heavy oil gas lift and established a coupled pressure-temperature model for annular injection of light oil gas lift wellbore using experimental results and basic theory of heat transfer. Model calculations show that the use of gas lift with diluted oil injection technology can significantly increase the capacity of heavy oil wells.…”
Section: Introductionmentioning
confidence: 99%
“…4 , 5 However, in countries like Venezuela, the dilution of bitumen with light oils is one such method used to increase the recovery factor, especially if coupled with either artificial lift or gas lift. 6 9 …”
Section: Introductionmentioning
confidence: 99%
“…The dilution of heavier crude with light crude to give a mixture with flow properties in between those of the initial components has been widely used to facilitate the transportation of bitumen. , However, in countries like Venezuela, the dilution of bitumen with light oils is one such method used to increase the recovery factor, especially if coupled with either artificial lift or gas lift. …”
Section: Introductionmentioning
confidence: 99%